2015
DOI: 10.1371/journal.pone.0143030
|View full text |Cite
|
Sign up to set email alerts
|

Chromodomain Helicase/ATPase DNA-Binding Protein 1-Like Gene (CHD1L) Expression and Implications for Invasion and Metastasis of Breast Cancer

Abstract: BackgroundChromodomain helicase/ATPase DNA-binding protein 1-like gene (CHD1L), also known as ALC1 (amplified in liver cancer 1 gene), is a new oncogene amplified in many solid tumors. Whether this gene plays a role in invasion and metastasis of breast cancer is unknown.MethodsImmunohistochemistry was performed to detect the expression of CHD1L in patients with invasive ductal carcinoma and normal mammary glands. Chemotaxis, wound healing, and Transwell invasion assays were also performed to examine cell migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Human ALC1 (Amplified in liver cancer 1), also known as CHD1L (Chromodomain-helicase-DNA-binding protein 1-like), is a remodeler encoded by a gene located within human chromosome 1q21, a region that is frequently amplified in hepatocellular carcinomas ( Ma et al., 2008 , Marchio et al., 1997 , Wong et al., 2003 ). Evidence suggests that ALC1 is a driver of oncogenesis ( Chen et al., 2009 , Chen et al., 2010 , Ma et al., 2008 , Mu et al., 2015 ). Additionally, ALC1 is involved in DNA damage repair ( Ahel et al., 2009 , Gottschalk et al., 2009 , Gottschalk et al., 2012 , Pines et al., 2012 , Sellou et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Human ALC1 (Amplified in liver cancer 1), also known as CHD1L (Chromodomain-helicase-DNA-binding protein 1-like), is a remodeler encoded by a gene located within human chromosome 1q21, a region that is frequently amplified in hepatocellular carcinomas ( Ma et al., 2008 , Marchio et al., 1997 , Wong et al., 2003 ). Evidence suggests that ALC1 is a driver of oncogenesis ( Chen et al., 2009 , Chen et al., 2010 , Ma et al., 2008 , Mu et al., 2015 ). Additionally, ALC1 is involved in DNA damage repair ( Ahel et al., 2009 , Gottschalk et al., 2009 , Gottschalk et al., 2012 , Pines et al., 2012 , Sellou et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ALC1 gene is frequently amplified and overexpressed in human hepatocellular carcinoma and numerous solid tumors. This overexpression is associated with lymph-node metastasis, tumor differentiation, and distant metastasis [ 42 , 43 ], suggesting that the ALC1 gene plays a role in invasion and metastasis of cancer cells. In contrast to the hypoxic microenvironment of solid tumors, malignant cells are exposed to a high concentration of oxygen during hematogenous metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 ] And in PC, CHD1L-Wnt/β-catenin was showed to be a novel pathway involved in PC progression. [ 11 ] Another study by Mu et al [ 14 ] showed that CHD1L could promote the invasion and metastasis of BC cells via the PI3K/Akt/ARK5/mTOR/MMP signaling pathway in BC. Furthermore, CHD1L was also involved in the progression of glioma, Sun et al [ 13 ] reported that suppression of CHD1L could induce cell cycle arrest and increase apoptosis in glioma cells, and the knockdown of CHD1L could significantly accelerate migration and invasion ability.…”
Section: Discussionmentioning
confidence: 99%